2020
DOI: 10.1101/2020.06.13.149690
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell screening of SARS-CoV-2 target cells in pets, livestock, poultry and wildlife

Abstract: A few animals have been suspected to be intermediate hosts of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). However, a large-scale

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 29 publications
1
35
0
Order By: Relevance
“…The low susceptibility of animals is probably attributed to restricting host-factors, e.g., functional ACE2 and specific proteases. A recent study has shown that the proportions of cells carrying both ACE2 and TMPRSS2 were high in cats, low in pigs, very rare in dogs and absent in chickens [ 163 ]. (5) To date, anthroponotic transmission is the main pathways for the infection and fatalities caused by SARS-CoV-2 in few companion and zoo animals, and no strong evidence for natural animal-to-human transmission, except for mink, which remains to be confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…The low susceptibility of animals is probably attributed to restricting host-factors, e.g., functional ACE2 and specific proteases. A recent study has shown that the proportions of cells carrying both ACE2 and TMPRSS2 were high in cats, low in pigs, very rare in dogs and absent in chickens [ 163 ]. (5) To date, anthroponotic transmission is the main pathways for the infection and fatalities caused by SARS-CoV-2 in few companion and zoo animals, and no strong evidence for natural animal-to-human transmission, except for mink, which remains to be confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…However, the experimental SARS-CoV infection was via simultaneous intranasal/oral/intraocular/ intravenous inoculation [29], thus the actual route(s) of SARS-CoV infection cannot be determined. Recently, several porcine cell lines have been shown to be permissive to SARS-CoV-2 infection [26,33]; in addition, single-cell screening studies showed that porcine ACE2/TMPRSS2 expression are compatible with infection [32]. In contrast to previous reports that some porcine cell lines are susceptible to SARS-CoV-2 infection, but show no CPE [26,33], we found that both ST and PK-15 cell lines are susceptible to infection and observed CPE after two or four passages, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Structure-based analyses predict that the SARS-CoV-2 Spike (S) protein receptor binding domain (RBD) binds the pig angiotensin-converting enzyme 2 (ACE2) entry receptor with similar efficiency compared to human ACE2 [31]. Single-cell screening also indicates that pigs co-express ACE2 and the protease TMPRSS2 (viral activating factor) in a variety of different cell lines, and SARS-CoV-2 replicates in various pig cell lines [2,26,32,33]. Despite these preliminary data indicating that pigs could be susceptible to SARS-CoV-2 infection, two recent studies revealed that intranasal inoculation of three and twelve pigs, respectively, with 10 5 pfu or TCID 50 of SARS-CoV-2 did not lead to any detectable viral replication or seroconversion [22,26].…”
Section: Introductionmentioning
confidence: 99%
“…However, the experimental SARS-CoV-1 infection was via simultaneous intranasal/oral/intraocular/intravenous inoculation [29], thus the actual route(s) of SARS-CoV infection cannot be determined. Recently, several porcine cell lines have been shown to be permissive to SARS-CoV-2 infection [26,33]; in addition, single-cell screening studies showed that porcine ACE2/TMPRSS2 expression are compatible with infection [32]. In contrast to previous reports that some porcine cell lines are susceptible to SARS-CoV-2 infection, but show no CPE [26,33], we found that both ST and PK-15 cell lines are susceptible to infection and observed CPE after two or four passages, respectively.…”
Section: Absence Of Immune Response In Sars-cov-2-inoculated Pigsmentioning
confidence: 99%
“…Structure-based analyses predict that the SARS-CoV-2 Spike (S) protein receptor binding domain (RBD) binds the pig angiotensin-converting enzyme 2 (ACE2) entry receptor with similar efficiency compared to human ACE2 [31]. Single-cell screening also indicated that pigs co-express ACE2 and the TMPRSS2 activating factor in a variety of different cell lines, and SARS-CoV-2 replicates in various pig cell lines [2,26,32,33]. Despite these preliminary data indicating that pigs could be susceptible to SARS-CoV-2 infection, two recent studies revealed that intranasal inoculation of three and twelve pigs, respectively, with 10 5 pfu or TCID50 of SARS-CoV-2 did not lead to any detectable viral replication or seroconversion [22,26].…”
Section: Introductionmentioning
confidence: 99%